General Principles of Orthopedics and Trauma - Iyer, K Mohan; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2013)
General Principles of Orthopedics and Trauma has been written to serve as a general introduction to the field of orthopedics and trauma. It is composed of a number of commonly seen disorders and with a corresponding therapeutic pathway, clearly explained with numerous x-rays and diagrams to aid the reader in their understanding of these useful procedures. The book is intended as a basic resource for trainees and junior surgeons, but will also be useful to more experienced specialists who require an easy to follow clinical guide to assist in day to day practice of orthopedic and trauma disorders.
Keywords: Orthopedics; Orthopedics; Surgical Orthopedics